The Chilean Maternal-Infant Cohort Study-II in the COVID-19 Era: A Study Protocol - Mujica-Coopman, María F.; Corvalán, Camila; Flores, Marcela; Garmendia, María Luisa (Frontiers in Public Health, 2022)
Pregnancy is a critical developmental window in which optimal maternal nutrition and health are key for pregnancy and infant development. The COVID-19 pandemic is considered as a ‘natural experiment’ in which maternal and infant nutrition and health challenges were faced especially in developing countries. Therefore, understanding the health consequences for mothers and infants living in the COVID-19 era is key to revisit public health measures focused on maternal and infant health. The current work aims to describe the design, methods, and descriptive information at recruitment and preliminary findings of the Chilean Maternal & Infant Cohort Study II (CHiMINCs-II) cohort. Methods. The CHiMINCs-II is an ongoing cohort that is part of the Chilean Maternal and Infant Nutrition Observatory of the South-East area of Santiago, Chile. In total, 1954 pregnant women beneficiaries of the public health systems and their offspring were recruited before 15 weeks of gestation and are followed across pregnancy (<15, 26-28, and 35-37 weeks of gestation) and up to 2 years of age in their offspring. Two studies are currently nested within the CHiMINCs-II cohort: 1) Breast Cancer Risk Assessment in Mothers (BRECAM) study, and 2) the CHiMINCs-COVID study. The primary objective of BRECAM study is to test the association between maternal metabolic indicators (i.e., insulin, glucose, insulin growth factor 1, and hemoglobin A1c concentrations) at early pregnancy (i.e., <15 and 26-28 weeks of gestation) and breast density 3 months after the cessation of lactation. For this purpose, we collect maternal obstetric, lifestyle, dietary intake, anthropometric, and biochemical information. The aim of the CHiMINCs-COVID study is to assess maternal dietary intake and mental health problems derived from the COVID-19 pandemic and their association with maternal and infant’s health and nutrition. Thus, we collected detailed information on dietary behaviors, mental health, and COVID-related information at each trimester, along with neonatal and infant nutritional information. Discussion. The findings of this study will provide novel and critical information to better understand maternal nutritional status, mental health, as well as infant growth and nutrition during the COVID-19 era. Trial registration. BRECAM study registration number NCT03920098 and CHiMINCs-COVID study registration number NCT01916603.